Posted 3 Jul 2013 · Report post Evaluate the following expression sqrt(2+sqrt(2+sqrt(2+sqrt(2+... repeating forever. 0 Share this post Link to post Share on other sites

0 Posted 3 Jul 2013 · Report post 2? correct. Care to explain your solution? 0 Share this post Link to post Share on other sites

0 Posted 3 Jul 2013 · Report post 2? correct. Care to explain your solution? Calculator. Every +sqrt(2) I pasted into the equation returned an answer that edged closer and closer to 2. It was more of a guess than an answer. 0 Share this post Link to post Share on other sites

0 Posted 3 Jul 2013 · Report post let x = sqrt(2+sqrt(2+sqrt(2+sqrt(2+... then ... 0 Share this post Link to post Share on other sites

0 Posted 4 Jul 2013 · Report post let x = sqrt(2+sqrt(2+sqrt(2+sqrt(2+... then ... I hope you're not intimating that -1 is also a solution! 0 Share this post Link to post Share on other sites

0 Posted 4 Jul 2013 (edited) · Report post let x = sqrt(2+sqrt(2+sqrt(2+sqrt(2+... then ... I hope you're not intimating that -1 is also a solution! nice work, but clearly -1 is a false solution and should be disregarded as such leaving only 2 Edited 4 Jul 2013 by BMAD 0 Share this post Link to post Share on other sites

0 Posted 4 Jul 2013 · Report post to expand on superprismatic let x = sqrt(2+sqrt(2+sqrt(2+sqrt(2+... so x = sqrt(2 + x) x^2 = 2 + x x^2 - x - 2 = 0 (x-2)(x+1) = 0 x =2, x =-1 x=-1 is impossible as the sqrt cannot give a negative answer (i.e. -1 = sqrt(1)) 0 Share this post Link to post Share on other sites

Posted · Report post

Evaluate the following expression

sqrt(2+sqrt(2+sqrt(2+sqrt(2+... repeating forever.

## Share this post

## Link to post

## Share on other sites